Unusual surge of acute hepatitis A cases in 2016 and 2017 in Malaga, southern Spain: characterization and relationship with other concurrent european outbreaks - Tapia-Paniagua, Silvana Teresa; González-Doménech, Carmen María; Vico Sevilla, José Alberto; Clavijo-Frutos, Encarnación; Martínez-Manzanares, Eduardo; Bardón de Tena, Paula (MDPI, 2023)
We aimed to describe the Hepatitis A virus (HAV) cases that arose in Malaga (Spain) in 2016 and 2017 when the European Centre for Disease Prevention and Control (ECDC) reported several outbreaks among men who have sex with men (MSM). Therefore, we conducted a retrospective study gathering demographic, clinical, and immunological data from the acute HAV patients attending our hospital between March 2016 and December 2017. Additionally, VP1/P2A region was amplified from serum samples, sequenced, and genotyped. We finally performed a phylogenetic analysis, including the HAV strains from the other European outbreaks. A total of 184 HAV cases were reported, with the highest number in March 2017. The cohort mostly comprised Spaniards (81.0%), males (84.8%), and MSM (72.3%), with a median age of 33.0 years (interquartile range (IQR) = 25.0-43.0). Most patients exhibited symptoms. In addition, a successful amplification and sequencing of the VP1/P2A region was performed in 25 out of 106 serum samples (23.6%). All the sequences belonged to the genotype IA, and 20 were phylogenetically related to VRD_521_2016, first described in the United Kingdom (UK). In conclusion, HAV cases emerged in Malaga in 2016 and 2017, showing an epidemic character phylogenetically related to the predominant strain first detected in the UK. Characteristics of the cohort were similar to those from the European outbreaks.
Keywords: Hepatitis; Hepatitis - Málaga - 2016-2017; HAV; MSM; Outbreak; Molecular epidemiology